Canadian Association of Optometrists/Canadian Ophthalmological Society Joint Position Statement: Effects of Electronic Screens on Children’s Vision and Recommendations for Safe Use - Optometrists, Canadian Association of; Society, Canadian Ophthalmological (Canadian Journal of Optometry, 2018)
The prevalence of electronic screen-related ocular symptoms in adult users is estimated to be as high as 50–90%. While the corresponding statistic in children is not known, the use of electronic screens by children has become more commonplace (at both home and school), begins earlier in childhood than in the past, and can last for long periods of time. The prevalence of electronic-screen symptoms in adults and the resultant guidelines for safe use should not be automatically applied to children. The visual and physical systems of children are different than those of adults, and still developing. In addition, children use screens differently and for different tasks. This policy reviews the current literature on ocular and visual symptoms related to electronic-screen use in children and provides evidence-based guidelines for safe use. The effect of screen-time on other cognitive and developmental milestones is beyond the scope of this statement.